Respectability and reform : Irish American women's activism, 1880-1920 - McCarthy, Tara M. (Irish studies (Syracuse, N.Y.), 2018)
"This project offers a national study of the different agendas and strategies pursued by Irish American women in the Gilded Age and Progressive Era, focusing on their roles in diaspora nationalism, the labor movement, and the suffrage movement."--Provided by publisher